Calling the patient's own name facilitates recovery from general anaesthesia: a randomised double‐blind trial. (27th October 2016) - Jung, Y. S.; Paik, H.; Min, S.‐H.; Choo, H.; Seo, M.; Bahk, J.‐H.; Seo, J.‐H.
Summary: People can hear and pay attention to familiar terms such as their own name better than general terms, referred to as the cocktail party effect. We performed a prospective, randomised, double‐blind trial to investigate whether calling the patient's name compared with a general term facilitated a patient's response and recovery from general anaesthesia. We enrolled women having breast cancer surgery with general anaesthesia using propofol and remifentanil. Patients were randomly allocated into two groups depending on whether the patient's name or a general term was called, followed by the verbal command – 'open your eyes!' – during emergence from anaesthesia; this pre‐recorded sentence was played to the patient using headphones. Fifty patients were allocated to the name group and 51 to the control group. Our primary outcome was the time from discontinuation of anaesthesia until eye opening. The mean (SD) time was 337 (154) s in the name group and 404 (170) s in the control group (p = 0.041). The time to i‐gel ® removal was 385 (152) vs. 454 (173) s (p = 0.036), the time until achieving a bispectral index of 60 was 174 (133) vs. 205 (160) s (p = 0.3), and the length of stay in the postanaesthesia care unit was 43.8 (3.4) vs. 47.3 (7.1) min (p = 0.005), respectively. In conclusion, using the patient's name may be an easy and effective method to facilitate recovery from general anaesthesia.